Direct Leaching of Zinc Concentrates at Atmospheric Pressure - R. W. Adams (The Minerals, Metals and Materials Society, 1990)
A new process has been developed for leaching zinc sulphide concentrates at atmospheric pressure using air or oxygen plus nitrogen dioxide in dissolved or gaseous form as? an oxygen carrier. The process is flexible and can cope with variations in the degrees of retention and regeneration of dissolved nitrogen dioxide in the leaching phase. By controlled addition of concentrate a leach solution with low residual nitrate concentration can be produced. Following separation by filtration of unleached solids and elementa1 sulphur and conventional oxidation/precipitation of dissolved iron, the leach liquor can be treated with metallic zinc to remove the remaining nitrate and other meta111c impurities such as copper, cadmium and cobalt to provide a solution suitable for electrolytic recovery of zinc. Pilot scale testing of the process .has given zinc recoveries in the high nlnet1es, production of a hi.gh grade jarosite-free Pb/Ag residue (50% Pb.) and a saleable high grade of elemental sulphur. .A wide range of concentrates can be treated containing substantial levels of lead and copper as well as zinc. Indicative cost estimates suggest that the new process is competitive with alternative procedures such as pressure leaching.